Tratamento biológico com lodo granular aeróbio de efluente de laticínio - Silva, Marcilene Bernardo (2021)
In the last decades, research on the use of aerobic granular sludge (AGS) has been gaining prominence in the area of effluent treatment as an alternative to replacing the use of traditional activated sludge, since this requires a large area for its installation, it needs to be used secondary clarifier and produces a large amount of sludge. In the present work, two sequential batch reactors, fed with synthetic dairy effluent, were operated in parallel. In the first reactor (R1), it was kept the conventional flocculent sludge from the activated sludge system and in the second (R2) the aerobic granular sludge(AGS). Both reactors showed high efficiency in the removal of BOD5 and COD, with values above 97% and 96%, respectively. Granular aerobic sludge samples indicated a higher concentration of phosphorus in the biomass. However, this fact did not reflect in a greater removal efficiency of this nutrient in the AGS reactor and both reactors obtained removal efficiencies higher than 70%. Regarding nitrogen, a satisfactory nitrification occurred in both reactors with total removal of ammonia. In relationto NTK, reactor R2 showed a higher removal (44%) than reactor R1 (29%). A greater removal of nitrogen in the reactor R2 was expected and can be explained by the reduced size of the formed granules, which can compromise the formation of the anoxic zone inside them. Such granules showed high sedimentation velocity (8.2 m.h-1), resistance (integrity coefficient = 0.22) and sedimentability (IVL30 = 32.30 mL.g-1). Furthermore, the analysis of extracellular polymeric substances indicated that proteins were the main components present in the granules